The IMF and the Latin American Debt Crisis : Seven Common Criticisms - Boughton, James (Washington, D.C. : International Monetary Fund, 1994)
The IMF played a key role in developing and implementing the debt strategy throughout the 1980s. That strategy not only overcame the crisis but also produced successful transformationsof several major economiesin Latin America. Nonetheless, the IMF's role has also been criticized on several grounds. This study examines seven such criticisms.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet